Single and combined effects of microplastics, pyrethroid and food resources on the life-history traits and microbiome of Chironomus riparius. (15th November 2021) - Varg, Javier Edo; Kunce, Warren; Outomuro, David; Svanbäck, Richard; Johansson, Frank
Abstract: There is growing evidence of widespread contamination of freshwater ecosystems with microplastics. However, the effects of chronic microplastic ingestion and its interaction with other pollutants and stress factors on the life-history traits and the host-microbiome of aquatic invertebrates are not well understood. This study investigates the effects of exposure to sediment spiked with 1 μm polystyrene-based latex microplastic spheres, an environmentally realistic concentration of a pyrethroid pesticide (esfenvalerate), and a combination of both treatments on the life-history traits of the benthic-dwelling invertebrate, Chironomus riparius and its microbial community. The chironomid larvae were also exposed to two food conditions: abundant or limited food in the sediment, monitored for 28 and 34 days respectively. The microplastics and esfenvalerate had negative effects on adult emergence and survival, and these effects differed between the food level treatments. The microbiome diversity was negatively affected by the exposure to microplastics, while the relative abundances of the four top phyla were significantly affected only in the high food level treatment. Although the combined exposure to microplastics and esfenvalerate showed some negative effects on survival and emergence, there was little evidence for synergistic effects when compared to the single exposure. The food level affected all life-history traits and the microbiota, and lower food levels intensified the negative effects of the exposure to microplastics, esfenvalerate and their combination. We argue that these pollutants can affect crucial life-history traits such as successful metamorphosis and the host-microbiome. Therefore, it should be taken into consideration for toxicological assessment of pollutant acceptability. Our study highlights the importance of investigating possible additive and synergic activities between stressors to understand the effects of pollutants in the life story traits and host-microbiome. Graphical abstract: Image 1 Highlights: Esfenvalerate and microplastics had negative effects on emergence, but not survival. The gut microbiome is affected by microplastics, but not by esfenvalerate. Food stress increased the negative effects of microplastics and esfenvalerate. Food level was an important driver of changes in the chironomid microbiome. Successful metamorphosis should be considered to assess if a pollutant is acceptable.